2009
DOI: 10.1002/art.24908
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor class A type I/II determines matrix metalloproteinase–mediated cartilage destruction and chondrocyte death in antigen‐induced arthritis

Abstract: Objective. Scavenger receptor class A type I (SR-AI) and SR-AII are expressed by macrophages in particular and bind and internalize a broad range of molecules (including endotoxins, apoptotic bodies, and oxidized low-density lipoprotein). This study was undertaken to investigate the role of SR-AI/II in mediating severe cartilage destruction in antigen-induced arthritis (AIA).Methods. AIA was induced in the knee joints of SR-AI/II ؊/؊ mice and wild-type (WT) controls. Joint inflammation and cartilage destructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Synovial tissue was weighed and put in Roswell Park Memorial Institute medium (Gibco, Invitrogen), enriched with penicillin/ streptomycin (100 units/mL potassium penicillin and 100 mg/mL streptomycin sulfate; Lonza, Walkersville, MD, USA) and 0.1 % bovine serum albumin (SigmaeAldrich) for 1 h at room temperature. S100A8/A9-complexes were measured in the wash-outs using sandwich enzyme-linked immunosorbent assay (ELISA), as described previously 32,33 . Keratinocyte chemoattractant (KC)-protein levels were measured with Luminex-technology (Biorad, Hercules, CA, USA), using magnetic milliplex beads (Millipore, Billerica, MA, USA) according to the manufacture's protocol.…”
Section: Synovial Wash-outsmentioning
confidence: 99%
“…Synovial tissue was weighed and put in Roswell Park Memorial Institute medium (Gibco, Invitrogen), enriched with penicillin/ streptomycin (100 units/mL potassium penicillin and 100 mg/mL streptomycin sulfate; Lonza, Walkersville, MD, USA) and 0.1 % bovine serum albumin (SigmaeAldrich) for 1 h at room temperature. S100A8/A9-complexes were measured in the wash-outs using sandwich enzyme-linked immunosorbent assay (ELISA), as described previously 32,33 . Keratinocyte chemoattractant (KC)-protein levels were measured with Luminex-technology (Biorad, Hercules, CA, USA), using magnetic milliplex beads (Millipore, Billerica, MA, USA) according to the manufacture's protocol.…”
Section: Synovial Wash-outsmentioning
confidence: 99%
“…Moreover, they imply that SR-AI/II could be involved in the development of autoimmunity. Indeed, it has been shown that induction of arthritis in SR-A-deficient mice resulted in decreased severity of disease compared with wild-type mice (van Lent et al, 2009).…”
Section: The Srcr Superfamily In Therapy and Diagnosismentioning
confidence: 99%
“…The extracellular function of S100A8-S100A9 is well documented as being a potent chemoattractant in mice and antimicrobial in humans (Nakatsuji and Gallo, 2011). S100A8 and S100A9 bind to several receptors including RAGE and CD36 (Gebhardt et al, 2008;van Lent et al, 2009), thereby affecting downstream signaling through NF-kB and AP-1 (Gebhardt et al, 2006;Grivennikov et al, 2010). These proteins were also identified as downstream targets of NF-kB in carcinogenesis (Né meth et al, 2009).…”
Section: Introductionmentioning
confidence: 99%